Perancangan Software The Smart Tourism Bali Dengan Android - Sulistiyanto Sulistiyanto (Joutica, 2022)
Tourism is an important sector in the development of a region. Especially for the island of Bali. It is not uncommon for Bali to be one of the largest contributors to tourism revenue in Indonesia. Almost every corner of the island of Bali has extraordinary tourism potential. One of them is Jembrana Regency, where Jembrana Regency is the gateway to the island of Bali which clearly has a very ideal geographical location and has its own tourist attraction. Along with technological developments, namely Smartphones and Android operating systems which are very widely used by humans. Android has an open source system where anyone can create an application that will be paired with the Android system. By utilizing the Geographic Information System (GIS) it is very easy to find tourist location points. and can easily add new tourist points. The Water Fall development method was chosen because it has structured stages with each stage having to be completed before the next stage. Therefore, there is a Curik Bali the Smart Tourism Application Design with Android which will be an application to introduce every tourist place in Jembrana Regency.